Mechanistic Study on Gold(I)-Catalyzed Unsaturated Spiroketalization Reaction - Sharma, Kamlesh (Letters in Organic Chemistry, 2022)
The mechanism of metal-catalyzed spiroketalization of propargyl acetonide is explored by employing DFT with the B3LYP/6-31+G(d) method. Acetonide is used as a regioselective regulator in the formation of monounsaturated spiroketal. The energies of transition states, intermediates, reactants and products are calculated to provide new insight into the mechanism of the reaction. The energetic features, validation of the observed trends in regioselectivity are conferred in terms of electronic indices via FMO analysis. The presence of acetonide facilitates a stepwise spiroketalization as it masks the competing nucleophile, and thus hydroxyl group present exclusively acts as a nucleophile. The vinyl gold intermediate 3 is formed from 2 via activation barrier TS1. This is the first ring formation, which is 6-exo-dig cyclization. The intermediate 3 is converted into allenyl ether 4, which isomerizes to the intermediate oxocarbenium ion 5 via activation barrier TS2. The intermediate 5 cyclizes to 6 via TS3. This is the second ring formation. The intermediate 6 on protodeauration turns into 6,6-monounsaturated spiroketal 7. It is concluded that acetonide as a protecting group serves the purpose, and thus a wide range of spiroketals can be prepared regioselectivity.
Keywords: regioselectivity